THE FUTURE DEVELOPMENT OF RUSSIAN EDUCATION: THE VIEW FROM RECTOR - Natalia V. Tikhomirova (Открытое образование (Москва), 2016)
How will Russian and global education change in the coming decade? What will be the educational environment and student’s educational tracks? Today, the university and each individual teacher are facing new challenges related to the conditions of rapidly altering information society. The article discusses current education development trends extensively affected by the contemporary social tendencies and describes the projected paths of long-term transformation of higher school.